Mr. Lincoln's high-tech war : how the North used the telegraph, railroads, surveillance balloons, iron-clads, high-powered weapons, and more to win the Civil War - Allen, Thomas B. (National Geographic, 2009)
Examines how Abraham Lincoln's interest in technology played a role in the outcome of the Civil War; and explains how the telegraph, railroads, surveillance balloons, and other inventions helped the North win the war and rebuild the economy.